Strategi Total Productive Maintenance (TPM) untuk Meningkatkan Kinerja Mesin PKS PT Tri Cahaya Sawit - Uni Pratama Pebrina Br Tarigan; Imran Yustin Sihombing; Raihan Syah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
Abstract: This study aims to analyze the implementation of TPM strategies in improving machine performance in Palm Oil Mills (PKS). Problems that often occur in PKS are high machine downtime, low equipment effectiveness, and operational disruptions that impact productivity decline. The methods used in this study include identifying machine failures, measuring Overall Equipment Effectiveness (OEE), and implementing TPM pillars such as autonomous maintenance, planned maintenance, and focused improvement. The results show that the implementation of TPM can improve machine reliability, reduce the frequency of breakdowns, and significantly increase the OEE value. In addition, operator involvement in routine maintenance activities also increases production process efficiency and reduces maintenance costs. Thus, the TPM strategy can be an effective solution in improving machine performance and operational productivity in Palm Oil Mills. Keywords: Total Productive Maintenance, TPM, Overall Equipment Effectiveness, Machine Performance, Palm Oil Mill.